Analysis of Ferrocement Slabs Using Finite Element Method - Mohamad, Ihsan Qasim (Basrah Journal for Engineering Sciences, 2012)
This paper is concerned with the application of finite element techniques to the nonlinear analysis of ferrocement slabs. Both material and geometric nonlinearities are considered in the analysis. Concrete compression is modelled by a plasticity model and smeared cracking approach is used for tensile cracking. Degenerated thick shell elements employing a layered discretization through the element are adopted. Analyzing of a ferrocement slab does validation of the proposed model.